EVALUASI SISTEM DRAINASE DALAM PENANGANAN GENANGAN DENGAN MODEL EPA SWMM VERSI 5.1 DRAINAGE SYSTEM EVALUATION IN FLOOD HANDLING WITH EPA SWMM MODEL VERSION 5.1 - WAHYUNI, ANNISA; FRANCHITIKA, RIZKY; NURMAIDAH, NURMAIDAH; KARTIKA, KARTIKA; BIMA, BIMA (JURNAL ILMIAH MAKSITEK, 2023)
Stagnant rainwater on the road disturbs the comfort of motorists and affects traffic and damages the road body. Gatot Subroto Street is the main road that connects Medan City and Binjai City which often has puddles at several points on its roads. Knowing these conditions, it is necessary to conduct drainage system research. This study aims to determine the planned flood discharge and concentration time in the water catchment area and provide solutions to the inundation problem. So that inundation and flooding caused by rain will no longer inundate the road surface and surrounding settlements. EPA SWMM (Environment Protection Agency Storm Water Management Model) is able to model the problem of quantity of runoff in urban areas and conditions that occur in the field by entering parameters recorded in real conditions. In this study, also evaluate an existing road drainage system and the factors that affect inundation and flooding. The methods used include the Normal distribution, Log Normal distribution, Gumbel distribution and Pearson Log Type III distribution and data compatibility test using the Smirnov-Kolmogorof test and Chi Square test. The results of the calculation of the planned flood peak discharge in the 5 year period is 2,813 m³/s and in the 10 year period it is 3,121 m³/sec while the concentration time in the water catchment area is 9.345 minutes or 0.156 hours. Comparison of the existing capacity of the channel and the planned flood discharge, it is found that the existing channel cannot accommodate the planned flood discharge, so it is necessary to re-plan the drainage channel. 0.746 m deep and 1.492 m wide; segment 3 with a depth of 0.868 m and a width of 1.737 m; segment4 with a depth of 0.567 m and a width of 1.134 m; segment 5 with a depth of 0.604 m and a width of 1.208 m; segment7 with a depth of 0.583 m and a width of 1.165 m.